"Ringing in the Common Love of Good": The United Farmers of Ontario, 1914-1926 - Wylie, Robin (Labour / Le Travail, 2001)
The article reviews the book, "Ringing in the Common Love of Good: The United Farmers of Ontario, 1914-1926," by Kerry A. Badgley.